A social - semiotic engagement with opposition social movements in online newspapers in Zimbabwe : case of #This Flag in the Herald online. - Chikwanha, Happiness (Midlands State University, 2020)
The study set out to establish the social-semiotic engagement of oppositional social movements with online newspapers with specific focus on The Herald Online and #This Flag in the period between Aril 2016 and June 2017. While a lot of work has been done around online media globally and in Africa and Zimbabwe in particular a gap still exists in how mainstream media, particularly The Herald newsier has used digital media in its engagement with opposition political forces, particularly opposition social movements which have been critical in the removal of entrenched authoritarian regimes elsewhere. The study took a qualitative approach and used archival digital data gathering methods and interviews whilst social-semiotics and critical discourse analysis were used to interpret and resent the data gathered. Theoretically the study employed Robert Merton’s structural strain theory to explain the causes of social activism whilst The Herald online texts were explored through Gramscian lenses. The study also employed Vannever Bush’s hypermedia theory in exploring the role of The Herald Online audiences in the engagement of the newsier and #This Flag. The study established that The Herald Online sought to defend its support of the government of the day resenting #This Flag as an imperialist project through the use of editorial cartoons, hard news and opinion reports. The study also established that The Herald Online sought to downplay #This Flag activities referring not to recognize the social movement by name. The study therefore recommended that The Herald Online would not lose anything by accommodating dissent in its mainstream reports yet maintain its pro-government position as a way of authenticating its defence of the status quo where the latter’s policies are justifiably beneficial to society.